Self-assessment of clinical competence of nursing students' at Slovak universities - Nemcová Jana; Hlinková Edita; Ovšonková Anna; Grendár Marian; Derňarová Eubica; Botíková Andrea; Poliaková Nikoleta; Kadučáková Helena; Slamková Alica; Jankechová Monica; Kajander-Unkuri Satu (Slovakia, 2025)
Background: Professional training and education of nurses are based on their clinical competences. Competence is an integration of knowledge, skills, and abilities, applied in nursing practice situations. By educating students in nursing, we strive for level of competencies to be consistent with the performance of the nursing profession.
Objective: The objective of the study was to analyze nursing students' self-assessment of competence levels at the time of graduation and to identify possible factors related the assessments of competence level. Sample and methodology: The research design had the character of a cross - sectional evaluation study, where The Nurse Competence Scale (NCS) was used to collect data. A total of 310 nursing students before completing the bachelor's degree, participated online to complete the NCS questionnaire, which represented 52.5% of the total number of graduating students at Slovak universities in the academic year 2018/2019.
Results: The overall self-assessment of the competence level reached a score of 57.0 (± 15.9; min 45.80, max 70.87), which represents a good level of competence. Statistically significant correlations were confirmed between the higher level of self-assessment of competences and factors related to education and the frequency of their use in practice. Self-assessed competence makes it possible to identify areas that can be further developed and covered it will be necessary to focus on curricula and student training.
Conclusion: Systematic self-assessment of competences, allows to assess readiness of nursing students to perform the profession of nurse in accordance with the expectations of practice. It also supports the responsibility of students for monitoring and motivation to study.